Technological characteristics of two wood species from Costa Grande, Guerrero, México - Pineda-Herrera, Elizandro; Pérez-Olvera, Carmen Paz; Dávalos-Sotelo, Raymundo; Valdez-Hernández, Juan Ignacio (Instituto de Ecología, A.C., 2012)
The anatomical, physical, and mechanical features, and drying time of wood from Enterolobiumcyclocarpum (Jacq.) Griseb. (Parota, Mimosoideae, Leguminosae) and Hura polyandra Baill. (Habillo,Euphorbioideae, Euphorbiaceae) collected in a semideciduous forest of Zihuatanejo de Azueta,Guerrero, Mexico, are described. For the anatomical description, pieces of 15 cm x 7 cm x 1 cm andslides 20 mm-thick, in transverse cross-section, tangential and radial directions and preparations ofdissociated material were used. For the physical and mechanical tests small clear specimens ofvarious dimensions, conditioned to a moisture content of 12%, were utilized. For each featuremeasured, univariate statistical analyses were performed and results were classified according to themean. For air drying time tests, boards and prisms were placed in a stack with spacers between them.The species have medium diameter vessels, extremely low uniseriate rays, and medium length fibers